Organisation of consumer accounting as a promising direction of accounting and analytical support for strategic management - G. A. Adamova (Вестник университета)
The research purpose is   to study the problems of  accounting and analytical support for profit management of the company on the basis of  the organisation of  сost and income accounting in  the context of  consumer groups. In  connection with the growth of   the share of   expenditures for promotion of   products to   the market and service, in  the work, the necessity of   сreating management accounting in   terms of   consumers being the company’s clients has been substantiated. Identification of   them as  objects will allow to  determine who causes the greatest costs of an economic entity, but does not bring enough profit, so   is not profitable. The possibilities of   such accounting have been examined to   achieve the objective of  strategic client assessment. The organisation stages of   the management accounting for consumers have been allocated, including ways of  grouping them for further analysis. The factors that determine the value of   clients for an  economic entity have been identified. The dependence of   the level of   the company’s costs on   the types of   activities related to   consumer service has been substantiated. Recommendations have been made on   the use of   intensive, operational, and temporary cost drivers to   allocate expenditures among consumer groups and determine their profitability for the company. The article offers the application of   a   client assessment matrix in  order to   identify strategically important consumers and those with whom it   is not worth maintaining long-term relations. In  conclusion, the possibilities of   using data of   the consumer accounting for management purposes are given.